Technology Adoption and Teaching performance: “A Moderating Role Age” - Mahat, Dipak (International Journal of Management and Business Intelligence, 2024)
Digital Skills Vs Experience: An Age-Driven Investigation of IT and Teacher Performance," explores the intricate interplay between age, information technology (IT), and teaching performance in the context of education. The study used an exploratory approach and used a structured questionnaire with a five-point scale to get first-hand information from 470 different teaching faculty members in Kathmandu Valley. To preserve participant secrecy and anonymity, ethical issues were crucial. The research methodology used powerful data analysis techniques that include correlation, ANOVA, and regression, as well as descriptive statistics. The study's model overview shows that Model H₁ is good at predicting how well teachers will do, as it explains 72.1% of the variation. The ANOVA test shows how important age and IT are as predictors of teaching success together. Regression analysis shows that both age and IT can be used as indicators, with IT having a much bigger effect. Part and partial connections provide more information about how age and IT are connected. This study fills in a gap in existing information about how well faculty members in Kathmandu Valley teach by focusing on the impact of age on their adoption and use of technology. It shows humanity a lot about how age, IT, and teaching ability change over time. This has important implications for educational policy, professional development, and using technology in the classroom.